Implementation of constructability concepts in construction phase in northern region / Siti Hafizan Hassan ... [et al.] - Hassan, Siti Hafizan; Ahzahar, Nadira; Ahmad, Hazrina (2010)
The concept of constructability in the United States or buildability in the United Kingdom emerged in the late of 1970s, which evolved from studies into how improvement can be achieved in overall project objective. It is an approach that links the design and construction process. The summary of definition of constructability is the opportunity in maximizing the use of construction knowledge and experience in planning, engineering, procurement and field operation to achieve overall project objectives. Constructability is use as one of the solution for the many problems that occurs in construction industry such as substantial numbers of changes, poor planning, cost overruns, wastage of materials, poor safety practiced and time delays. The objective of this research is to study constructability concepts in construction project, to identify the level of importance of constructability concepts in construction projects and to identify the level of application of constructability in construction project. It is focused on the construction player in Northern Region. The data were collected by distributing the questionnaire to the construction management player. The data were analyzed using SPSS and average index. From the findings it is found that the first three importance concept are ‘Carry out Through Investigation of the site’, ‘Involves Construction Knowledge and Experience’ and ‘Site Layout Promote Efficient Construction’. Besides that the levels of importance of constructability concepts are conclude as important since averagely 15-40% of the respondents agreed on its importance. While the level of application is intermediate since the respondents who said it is high application is averagely 15-40%.